The attribution of gendered meanings in Chinese musical instruments - Ang, Ying Xuan (2016)
Research has shown that there is significant gendered associations of Western musical instruments in young children or students in Western schools. This paper thus attempts to understand how musicians attribute gendered meanings to musical instruments with a focus on Chinese traditional instruments and established musicians in modern Chinese orchestras in the context of Singapore by first uncovering gendered associations of these instruments and understanding the relationships that musicians have with their instruments. Results showed that musicians attribute gendered meanings in two ways. Firstly, through the gender-typing of instruments where the process of categorization is used to gender-type instruments along three main categories – physical, auditory and visual. Secondly, through the idea of personhood that musicians attribute to their instruments when building a relationship with it.